Comparative study of effectiveness and safety between non-Descemet stripping endothelial keratoplasty and Descemet stripping endothelial keratoplasty for endothelial decompensation - Huang, Minghai; Yin, Guina; Hoang, Thuthuy; Wu, Zhifeng; Teng, Jian; Liang, Yanqing; Zhang, Zhuoyuan; Wei, Dongmei (Frontiers in Medicine, 2025)
PurposeTo compare the potential effectiveness and safety of non-Descemet stripping endothelial keratoplasty (nDSEK) and Descemet stripping endothelial keratoplasty (DSEK) in treating endothelial decompensation.MethodsA retrospective comparative analysis was conducted on patients with endothelial decompensation who underwent either nDSEK or DSEK procedures between August 2017 and January 2024. Participants were observed for a minimum duration of 12 months. The study documented key variables like best corrected visual acuity (BCVA), endothelial cell density (ECD), endothelial cell loss (ECL), and any issues that occurred during the follow-up period.ResultsA total of 85 eyes from 85patients (nDSEK n = 40 eyes, DSEK n = 45 eyes) were ultimately included in the study for analysis based on the inclusion and exclusion criteria. The mean BCVA (logMAR) showed significant improvement from the preoperative measurement of 1.66 ± 0.26 to 0.37 ± 0.11 in nDSEK eyes and from the preoperative 1.68 ± 0.24 to 0.36 ± 0.10 in DSEK eyes, respectively, at postoperative 12 months. However, there was no statistically significant difference in the improvement of BCVA between the nDSEK and DSEK eyes (p = 0.605). The mean donor ECD decreased from the preoperative 2,814 ± 85 cells/mm2 to 1,195 ± 216 cells/mm2 (ECL 57.5%) in nDSEK eyes and from the preoperative 2,889 ± 125 cells/mm2 to 1,266 ± 285 cells/mm2 (ECL 56.2%) in DSEK eyes, respectively, at postoperative 12 months, with no significant difference between the nDSEK and DSEK eyes (p = 0.192). The occurrence of various complications (e.g., graft dislocation, acute hypertension, primary graft failure, graft rejection) was comparable between nDSEK and DSEK eyes.ConclusionnDSEK eliminated the descemetorhexis step but yielded a comparable clinical outcome in effectiveness and safety compared to DSEK for treating endothelial decompensation.